Mortality risk prediction in octogenarians undergoing emergency colorectal surgery: a tertiary center experience and systematic review of the literature - Brolese, Marco; Vittori, Arianna; Todisco, Matteo; Zuin, Nadine; Cusano, Vanessa; Valli, Valeria; Vallese, Lorenzo; Baldan, Nicola; Valmasoni, Michele; Da Dalt, Gianfranco; Friziero, Alberto (Frontiers in Surgery, 2025)
ObjectiveSurgical colonic emergencies frequently occur in elderly patients. In these cases a comprehensive preoperative assessment is crucial to tailor surgical invasiveness to individual risk profiles and potentially improve clinical outcomes. The aim of our study was to identify predictors of in-hospital mortality in octogenarians undergoing emergency colorectal resections, and compare the short-term outcomes between elderly and younger patients.MethodsThis study included patients who underwent emergency colorectal resections at Our Department between January 2020 and December 2024. Exclusion criteria were age <18 years and palliative surgery. Patients were stratified into two cohorts: octogenarians (≥80 years, Group 1) and patients aged <80 years (Group 2). Baseline characteristics, perioperative variables, and short-term outcomes were compared and analyzed. A systematic review (PROSPERO: CRD420251050770) was conducted to identify the studies evaluating outcomes of emergency colorectal resections in octogenarians. MEDLINE (via PubMed), EMBASE, and EBSCOhost were searched from database inception to April 2025.ResultsGroup 1 and Group 2 included 82 and 130 patients with median ages of 84 and 67 years, respectively. The in-hospital mortality rate was 24% in octogenarians and 8% in younger patients (p < 0.001). Multivariate logistic regression identified hyperlactatemia as an independent negative prognostic factor for in-hospital mortality in octogenarians (p = 0.01). Through a systematic review of the literature we identified 12 publications, and the mortality rate ranged between 7.0 and 37.8%.ConclusionsEarly identification of prognostic factors can improve clinical outcome in emergency scenarios. Our systematic review, the first reported in the literature, provides a comprehensive perspective in this field.